Optimum multiple tuned mass dampers for structures under the ground acceleration based on DDMF and ADMF. - Li, Chunxiang (Earthquake engineering & structural dynamics.)
Multiple tuned mass dampers (MTMD) consisting of many tuned mass dampers (TMDs) with a uniform distribution of natural frequencies are taken into consideration for attenuating undesirable vibration of a structure under the ground acceleration. A study is conducted to search for the preferable MTMD which performs better and is easily manufactured from the five available models (i.e. MTMD-1 - MTMD-5), which comprise various combinations of the stiffness, mass, damping coefficient and damping ratio in the MTMD. The major objective of the present study then is to evaluate and compare the control performance of these five models. The structure is represented by its mode generalized system in the specific vibration mode being controlled by adopting the mode reduced order approach. The optimum parameters of the MTMD-1 - MTMD 5 are investigated to reveal the influence of the important parameters on their effectiveness and robustness using a numerical searching technique. The parameters include the frequency spacing, average damping ratio, tuning frequency ratio, mass ratio and total number. The criteria selected for the optimum searching are the minimization of the maximum value of the displacement dynamic magnification factor (DDMF) and that of the acceleration dynamic magnification factor (ADMF) of the structure with the MTMD-1 - MTMD 5 (i.e. Min.Max. DDMF and Min.Max.ADMF). It is demonstrated that the optimum MTMD-1 and MTMD-4 yield approximately the same control performance, and offer higher effectiveness and robustness than the optimum MTMD-2, MTMD-3, and MTMD-5 in reducing the displacement and acceleration responses of structures. It is further demonstrated that for both the best effectiveness and robustness and the simplest manufacturing, it is preferable to select the optimum MTMD-1.